AB0696 Predictors of poor response to 6-months methotrexate therapy in a juvenile idiopathic arthritis cohort of patients. (23rd January 2014) - Marques, R.; Ramos, F.; Perpétuo, I.; Fernandes, S.; Furtado, A. C.; Mourão, A. F.; Martins, F.; Fonseca, J. E.; Pereira da Silva, J. A.
Abstract : Background: The identification of predictive factors of poor response to methotrexate (MTX) in juvenile idiopathic arthritis (JIA) patients could contribute to optimize the treatment strategy, namely by the earlier introduction of biological treatments. Objectives: To identify baseline clinical or laboratorial predictive factors of MTX poor response at 6 months in patients with JIA. Methods: In a cohort of 141 JIA patients registered in Reuma.pt (the Portuguese Register of Rheumatic Diseases)we selected patients diagnosed after 2000 and that were treated at least for 6 months with MTX (at least 10mg/m 2 ). Bivariate and multivariate logistic analyses were used to identify the predictors for non-response to MTX treatment during the first 6 months of treatment. Non-response to MTX was defined according the American College of Rheumatology pediatric 70 criteria. Concomitant treatment with NSAIDs and corticosteroids up to 10mg was allowed for all treatment groups. For this analysis we included: sex, age, age at disease onset, subtype, disease duration, rheumatoid factor (RF), ANA, HLA-B27, uveitis, age at MTX onset, disease duration until the start of MTX, baseline physician and patient/parents VAS, baseline active and limited joints and ESR. Results: From the 58 patients identified, 23 were excluded (2 started biological therapy before 6 months, 3 were on concomitant DMARD's, 12 had insufficient data, 1 developed criteria for systemic lupus erythematosus, 3 had interrupted MTX and 2 were loss for follow-up). From our population 43% have achieved ACR-ped 70 response and the remaining 57% did not reach this response criterion. We found no differences in the parameters analyzed between the 2 groups, except the age of MTX onset (p=0.03; responders 5 [3-11.5], non-responders 17.5 [11-22.6]) and parents/patients VAS (p=0.047; responders 50 [40.9-61.6], non-responders 20 [13-53.6]). We observed that older age at the beginning of MTX and lower patient/parents VAS were independently associated with poor response to MTX therapy. Accordingly, we have introduced in a logistic regression model both of these parameters. After multivariate analysis, age at the beginning of MTX was the only determinant independently associated with ACR-ped 70 non responders (p=0.05; OR 0.83). Conclusions: In our cohort of JIA patients, older age at MTX onset was correlated with poorer response to a 6-month MTX course. Disclosure of Interest: None Declared